Novel sulfated octa- and decasaccharides from squid cartilage chondroitin sulfate E: Sequencing and application for determination of the epitope structure of the monoclonal antibody MO-225 - Sarama Sathyaseelan Deepa (2018)
A mixture of octa- and decasaccharides obtained by the digestion with the hyaluronidase of chondroitin sulfate E derived from squid cartilage was subfractionated into 20 and 23 different components, respectively, by anion-exchange HPLC. MALDI-TOF/MS was used to assign the sugar and sulfate composition of the putative octa- and decasaccharides, and a disaccharide composition analysis revealed the building blocks to be A- [GlcUAβ1- 3GalNAc(4S)], C-[GlcUAβ1 -3GalNAc(6S)], and E-[GlcUAβ1-3GalNAc(4S,6S)] units, where 4S and 6S represent 4-O- and 6-O-sulfate, respectively. The sequences of these octa- and decasaccharides were determined at low picomole amounts by a combination of enzymatic digestions with chondroitinases in conjunction with anion-exchange HPLC. Sequencing revealed that each fraction is a mixture of a major component together with one to three minor components, reflecting the heterogeneity of the parent polysaccharide. Among the 11 different octasaccharide sequences reported here, 8 are novel, while all of the 6 decasaccharide sequences are novel, and this is the first report of the sequencing of CS oligosaccharides longer than octasaccharides. The reactivity of the monoclonal antibody MO-225 with octa- and decasaccharides tested with an oligosaccharide microarray revealed that a CS-E decasaccharide is the minimal requirement for antibody recognition. Among the 6 decasaccharides, only E-E-E-E-C was recognized by MO-225, suggesting the requirement of a C-unit at the reducing end and also the importance of chain length, which in turn may indicate the importance of the conformation acquired by this specific sequence for antibody recognition. © 2007 American Chemical Society.